PENGELOLAAN ALOKASI DANA DESA DALAM MEWUJUDKAN GOOD GOVERNANCE - Rigel Nurul Fathah; Teti Anggita Safitri (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2018)
This study focuses on the application of the principle of accountability in the management of Village Fund Allocation. This study aims to 1) Know the accountability system for managing Village Fund Allocation in Sardonoharjo Ngaglik Sleman Village in 2017. 2) Knowing the obstacles in the implementation of the Village Fund Allocation management in Sardonoharjo Ngaglik Sleman Village in the year 2017. 3) Measuring Village Financial Performance in Sardonoharjo Ngaglik Sleman Village in 2017. This research is a qualitative research in which the researcher conducted in-depth interviews with the informants to gather information so that objective research on village fund allocation was obtained, this was done considering that in-depth interviews were the right research strategy to find out in detail both the village government and village officials. The conclusion of this study is that 1) Planning and Implementation of the Village Fund Allocation program in Sardonoharjo Village has implemented the principles of participatory, responsive, transparent. 2). Village Fund Allocation Accountability both technically and administratively has been good, but in terms of administrative accountability is constrained by delays in reports from the dukuh and the village parties have difficulty in implementing the Village Financial System (SISKEUDES).